Relationship of Sociodemography and Dental Visits With Dental Caries and Oral Hygiene At Kapuk 03 Pagi Public Elementary School in West Jakarta - Theresia, Tiarma Talenta; Louisa, Marie; Kristanto, Cindy Vania; Winson, Angela (Jurnal Kesehatan Gigi, 2024)
In Indonesia, children still have a high incidence of dental caries; among children aged 5 to 9 years, the rate was 92.6%, and among those aged 10 to 14 years, it was 73.4%. Risk factors that contribute to childhood caries include child behavior and dental care utilization, family dynamics, and environmental. The health of teeth and mouths can be achieved with good oral hygiene. Oral hygiene can be influenced by gender, age, parental education, and dental visits. The study aimed to determine the relationship between sociodemography and dental visits with dental caries and oral hygiene at public elementary school in West Jakarta. This research is a cross sectional observational analytic using a questionnaire involving 174 respondents and direct examination of the oral cavity to obtain dental caries and oral hygiene. The results show that the p-values for the association between dental caries and gender, age, father’s education, mother’s education, and dental visits are 0.924, 0.588, 0.222, 0.172, and 0.115, respectively, all of which are greater than the significance level of 0.05. Similarly, the p-values for the association between oral hygiene and gender, age, father’s education, mother’s education, and dental visits are 0.231, 0.068, 0.064, 0.509, and 0.427, respectively, all exceeding the significance level of 0.05. In conclusion, the dental caries status of students at Kapuk 03 Pagi Public Elementary School is low, and their oral hygiene status is good. There is no correlation between dental caries and oral hygiene with gender, age, father's education and mother's education, and dental visits.